Meningkatkan Hasil Belajar Peserta Didik Menggunakan Media Quizizz pada Mata Pelajaran Bahasa Indonesia di SMA Negeri 2 Medan Kelas X - Alwi Abdullah Alwi; Rita; Afri Amelia (STKIP Subang, 2025)
This study aims to improve students' learning outcomes in Indonesian language subjects through the application of digital learning media Quizizz. The background of the study is based on the low interest and learning outcomes of students in Indonesian language subjects which are considered boring. Quizizz, as an interactive game-based platform, is used to create a fun learning atmosphere and in accordance with the characteristics of the current digital generation. This study uses the Classroom Action Research (CAR) method with 35 students of class X of SMA Negeri 2 Medan as subjects. Data collection techniques were carried out through observation, pre-test, learning with Quizizz, and post-test. The results of the study showed a significant increase in student learning outcomes after using the Quizizz media, with an average score increasing from 59 (pre-test) to 88 (post-test). Thus, the use of Quizizz media has proven effective in increasing student motivation and learning outcomes in Indonesian language lessons.